Histology of Mice Skin Tissue Based on in Vivo Evaluation of the Anticancer Extracts of Marine Sponge Aaptos Suberitoides - Awik Puji Dyah Nurhayati; Dewi Hidayati; Rarastoeti Prastiwi; Sitarina Widyarini; Sukardiman Sukardiman; Wijayanti Pujitono (IPTEK The Journal for Technology and Science, 2011)
The sponge Aaptos suberitoides can produce high secondary metabolite with some farmocological activities as antimicrobial, antiviral, antiinflamatory, and anticancer agents. The purpose of this research is to find out correlations between activities of the etanol extracts of marine sponges Aaptos suberitoides on the cancer growth of subcutaneous mice (Mus musculus) injected by Benzo(a)piren. For the purpose the mice were divided into six groups, i.e. I, II, III, IV, V, and VI. Each group was treated with carcinogenic inductions by intravenously injecting the Benzo(a)piren concentration of 0.3g/0.2 ml oleum olivarum. After the cancer was appeared at the fifteenth day, the mice were treated by the anticancer extracts of marine sponges Aaptos suberitoides with concentrations of 500 mg/kg BB (Group IV), 1000 mg/kg BB (Group IV), and 1500 mg/kg BB (Group IV). The treatments were orally done each day for two weeks. At the twentieth week, subcutaneous cancer tissues were taken to make histological preparates using a parafin method. Result of the histological observation indicates that cancer in the mice was fibrosarcoma characterized by the thickening dermis layers, necrosis, mitosis, and nuclear polymorphsm. Necrosis, mitosis, and nuclear polymorphism occurred in Groups II, IV, V, and VI, and did not in Groups I and II. Presentation of necrosis was 20-60%, mitosis was in 3-4 cells, and nuclear polymorphism was 100%. Result of the statistical analyses by using the Kruskal-Wallis method and the Pair Comparison test indicates that the anticancer extracts of marine sponges with the concentrations of 500 mg/kg BB, 1000 mg/kg BB, and 1500 mg/kg BB had no activity inducing mice skin cancer.